THE PRINCIPLE OF OPENNESS TO THE AUTHORITY OF WAHANA MUSIK INDONESIA COLLECTIVE MANAGEMENT INSTITUTIONS (LMK) (WAMI) IN MANAGING THE ECONOMIC RIGHTS OF SONG AND/OR MUSIC CREATORS - Nur, Nurwati; Budiman, Teguh (Fakultas Hukum Universitas Djuanda, 2023)
On March 2022, the entertainment world, especially the music industry in Indonesia, was shocked by the release of musician Ahmad Dhani from the Collective Management Institute (LMK WAMI), where he has been taking shelter so far in managing royalties for his economic rights as a songwriter and musician. As we know that Ahmad Dhani is the frontman of the Dewa 19 music group and also oversees several famous musicians and artists in Indonesia, even his work in the music industry has gone international where he founded the band TRIAD with musicians from Australia. There is no doubt about Ahmad Dhani's achievements in the music industry. The works that he created with the band Dewa 19 or Ahmad Dhani himself have graced the entertainment scene and music lovers in Indonesia since the early 90s. His works, entitled Kangen, Cukup Siti Nurbaya, Elang, Pupus, Roman Picisan, Risalah Hati and many others are always included in the Top List songs of the best songs in Indonesia. Even his songs are timeless, where there are still many millennial generations who know and recreate Ahmad Dhani's songs